Endoscopic gastric polyp removal (Colombia Medica, 1988)
Gastric polyps are potentially malignant lesions and should, therefore, be resected. Endoscopic gastric polypectomy is the accepted method of treatment with a very low complication rate. The experience with endoscopic gastric polypectomy ever since the method was introduced at the Hospital Universitario del Valle four years ago is presented. Thirthy-three polyps were resected in 27 patients. The microscopic diagnoses in 24 cases were revised.